Caracterização e análise dos efeitos associados à falha de isolamento em cabos cobertos de redes de distribuição compactas frente a surtos atmosféricos - Ronaldo Eugenio de Souza Filho (2018)
The effects associated with lightning direct or nearby strikes to the power distribution grids are able to induce high overvoltages on the lines. Such overvoltages are often the cause of breakdown. Aiming to minimize the occurrence of outage due to lightning, some Brazilian power utility companies are replacing their traditional systems bare cables supported by ceramic insulators in wood cross arms by overhead compact distribution lines. This configuration consists of covered cables, polymeric spacers and polymeric insulators. In the last years, a thorough investigation has been developed at Lightning Research Center. This research is dedicated to the role of the dielectric layer of the cables on the increment of voltage withstand. In this context, the present thesis is related to the comprehension of the phenomena and the effects associated to the breakdown process in covered cables. In this work, experimental results of tests with impulse voltages performed with single- and three-phase structures are presented. Such results compose a set of parameters that model the effects of the breakdown process on compact overhead lines due lightning overvoltage. The main parameters are: (i) minimum and mean values of the disruptive voltages, (ii) time-to-failure, and (iii) the main events related to the breakdown process, such as charge accumulation over the insulation which is responsible for modify the characteristics of the disruptive process , the occurrence of partial disruptive discharges and the pinhole formation. The obtained results indicate that the use of covered cables promotes a weighty increase of the withstand voltage level compared to the use of bare cables at least 40%. The results have also indicated the polarity effect on the impulse withstand levels of covered cables. When the insulating layer is present, the breakdown voltage values for negative impulses are at least 8% lower than the values for positive impulses. Tests performed with punctured cables have shown a trend of increase of the voltage value with the increase of the distance between the damage and the insulator. In addition, cables that had already been in operation before the tests showed a performance very similar to that obtained for new ones